1990
DOI: 10.1139/x90-010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of self-, cross-, and no pollination on ovule, embryo, seed, and cone development in western red cedar (Thujaplicata)

Abstract: The effects of self-, cross-, and no pollination on cone size, filled seed, pollination efficiency, ovule development, and seed efficiency were tested on rooted ramets of six western red cedar (Thujaplicata Donn) clones. To fully develop, ovules must be pollinated with viable pollen and cones must have a minimum of one developing seed. The seed potential was constant among clones and not affected by pollination. The greatest loss of potential seed resulted from a failure of ovules to be pollinated, followed cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…Several factors affect the production of high quality seeds, such as insect infestation (El Atta 1993, Dajoz 2000, Bates et al 2000, pollination failure and post-zygotic degeneration (Owens et al 1990, El-Kassaby et al 1993, infection by seed borne pathogens (Pritam and Singh 1997), environmental conditions during seed development (Gutterman 2000) as well as the genetic constitution (Bazzaz et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors affect the production of high quality seeds, such as insect infestation (El Atta 1993, Dajoz 2000, Bates et al 2000, pollination failure and post-zygotic degeneration (Owens et al 1990, El-Kassaby et al 1993, infection by seed borne pathogens (Pritam and Singh 1997), environmental conditions during seed development (Gutterman 2000) as well as the genetic constitution (Bazzaz et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The outcrossing rate for most conifer species is above 80% (52 species, mean 83.5%; reviewed in O'Connell, 2003). While western redcedar produces abundant viable selfed seeds (Owens et al, 1990), inbred trees produced by self-fertilization have shown significant reduction in growth rate (ca. 10%) compared to noninbred trees (Russell et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The number of seed harvested is generally considered an indication of breeding success (Johnsson 1976). However, pre-zygotic barriers (before fertilisation) can reduce the numbers of mature cones or seed harvested, while post-zygotic barriers (after fertilisation) can increase the number of hollow seeds without affecting the number of seed extracted from the cones (Critchfield and Kinloch 1986;Owens et al 1990). Therefore, estimating the time (in weeks) after pollination that fertilisation might occur can help to estimate viable seed set during interspecific hybridisation and make subsequent tissue-culture (embryo rescue and micropropagation) projects more effective (Cisneros and Tel-Zur 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although pollination and fertilisation in Pinus species may yield a large number of mature cones filled with seed, some might be non-viable due to pollination failure or post-zygotic degeneration (Owens et al 1990;El-Kassaby et al 1993). Seeds need to be extracted, and viable seeds separated from non-viable ones (Bramlett et al 1977) before sowing.…”
Section: Introductionmentioning
confidence: 99%